Enhanced rate of formation of trigonal phase in blends of homogeneous isotactic propylene-1-hexene copolymers. (1st May 2015) - Janani, Hamed; Alamo, Rufina G.
Abstract: Blends of a miscible pair of propylene-1–hexene (PH) copolymers with 11 and 21 mol% of 1-hexene have been studied in reference to their polymorphic behavior, lamellar structure and crystallization kinetics using in situ WAXD, DSC and AFM. As pure components, PH21 crystallizes in a trigonal packing in the whole range of undercooling while PH11 develops monoclinic crystallites at low undercooling or the mesomorphic form at high undercooling. In the blends, the level of overall crystallinity obtained from WAXS increases from 17 to 25% and scales directly with increasing content of PH21. Due to differences in crystallization kinetics, two separate populations of crystallites develop in the blends, each of a different polymorph. As expected, the content of trigonal phase decreases with increasing PH11, however, the rate of formation of trigonal phase in the whole range of undercooling increases with addition of PH11, which as a pure component does not form trigonal phase. This unexpected enhanced kinetics of formation of trigonal phase with blending is attributed to the increasing composition of 1-hexene in the melt during evolution of the monoclinic phase in the first stage of isothermal crystallization of the blends. Graphical abstract: Highlights: PH11/PH21 blends show double stage isothermal crystallization kinetics. Monoclinic crystals form first, trigonal crystals follow. The rate of formation of trigonal phase in the blends is enhanced with PH11 content. Faster rate is due to increased 1-hexene content in the melt during the first crystallization stage.